2006
DOI: 10.1189/jlb.0505282
|View full text |Cite
|
Sign up to set email alerts
|

Bovine polymorphonuclear cells passively acquire membrane lipids and integral membrane proteins from apoptotic and necrotic cells

Abstract: Immune cells can acquire membrane fragments and integral membrane proteins from dead and dying cells or in the case of immature dendritic cells, from live cells. While investigating the possibility that bovine polymorphonuclear cells (PMNs) might present antigen, coculture assays confirmed that integral membrane proteins were transferred rapidly and efficiently to bovine PMNs from a variety of apoptotic and necrotic cells. Specifically, we observed that PMNs rapidly acquired proteins such as major histocompati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 27 publications
4
31
0
1
Order By: Relevance
“…In separate experiments with neutrophils isolated from the blood of two different donors, we found that between 50 and 75% of the bound RTX was removed from Al488 RTX-opsonized Daudi cells. This result is in agreement with the findings of Whale et al which revealed that neutrophils can indeed remove ligands from other cells (54).…”
Section: Neutrophils Take Up Rtx From Opsonized Daudi Cellssupporting
confidence: 83%
“…In separate experiments with neutrophils isolated from the blood of two different donors, we found that between 50 and 75% of the bound RTX was removed from Al488 RTX-opsonized Daudi cells. This result is in agreement with the findings of Whale et al which revealed that neutrophils can indeed remove ligands from other cells (54).…”
Section: Neutrophils Take Up Rtx From Opsonized Daudi Cellssupporting
confidence: 83%
“…36 Our study provides a foundation from which to explore the mechanism(s) of trogocytosis further. Because trogocytosis is performed not only by lymphocytes but also by most hematopoietic cells [9][10][11][12][13] and is proposed to have important physiopathologic 6,17 and possibly therapeutic 12 consequences, exploring the mechanisms of trogocytosis is of a crucial importance and may open new ways to manipulate the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…6 Initially, using well-characterized murine models of antigen-specific lymphocytes, we made this observation in CD8 ϩ CTLs but, later, we showed that CD4 ϩ T cells and B cells also perform trogocytosis (ie, they acquire membrane-anchored antigen in fragments of membrane). 7,8 Trogocytosis has since also been reported for most other hematopoietic cells including natural killer (NK) cells (see RodaNavarro and Reyburn 9 for a review), dendritic cells, 10 monocytes, 11,12 and neutrophils, 13 indicating that antigen recognition by antigen receptors is not the only molecular trigger for trogocytosis. Worthy of note, activated but not resting CD4 ϩ and CD8 ϩ T cells were shown to acquire membrane patches from target cells in the absence of antigen and independently of the TCR.…”
Section: Introductionmentioning
confidence: 99%
“…paratuberculosis infection and 1 day prior to euthanizing. PBMCs were isolated following a previously described protocol (20). Briefly, blood was centrifuged at 1,400 ϫ g for 20 min at room temperature before collecting the buffy coat and resuspending cells in 35 ml Ca 2ϩ -and Mg 2ϩ -free PBS (PBSA) containing 0.1% EDTA.…”
Section: Methodsmentioning
confidence: 99%